The influence of hydrogen on chip formation in cutting Ti-6Al-4V alloys. Issue 1 (March 2017) - Fu, Xuesong; Chen, Guoqing; Yang, Qi; Sun, Zhonggang; Zhou, Wenlong
Abstract The paper investigated how hydrogen, introduced via thermal diffusion, influenced the formation and morphology of chips formed by cutting Ti-6Al-4V alloys. The chips' microstructure and characteristics were studied by using optical microscopy (OM), X-ray diffraction (XRD), and scanning electron microscopy (SEM). Experimental results demonstrated that with an increase in plasticity, the lamellar chips transformed to saw-tooth chips. Metallurgical analysis suggested that the saw-tooth chips formed because of thermoplastic instability caused by large plastic deformation. In contrast, the lamellar chips formed because of crack initiation.